2022
DOI: 10.3389/fphys.2022.892247
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Mass, Blood Volume and VO2max of Trained and Untrained Children and Adolescents Living at Different Altitudes

Abstract: Introduction: To a considerable extent, the magnitude of blood volume (BV) and hemoglobin mass (Hbmass) contribute to the maximum O2-uptake (VO2max), especially in endurance-trained athletes. However, the development of Hbmass and BV and their relationships with VO2max during childhood are unknown. The aim of the present cross-sectional study was to investigate Hbmass and BV and their relationships with VO2max in children and adolescents. In addition, the possible influence of endurance training and chronic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Similarly, our latest research involving a large sample of children and adolescents from both sexes concluded that the associated effects of endurance training on Hbt and BV is only observed after the onset of puberty. 13 Our results, shown in Fig. 2 , Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Similarly, our latest research involving a large sample of children and adolescents from both sexes concluded that the associated effects of endurance training on Hbt and BV is only observed after the onset of puberty. 13 Our results, shown in Fig. 2 , Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding studies focused on the adolescent population, comparable results have been reported for elite swimmers 46 and skiers, 47 , 48 although a wide inter-individual variability was clear in the erythropoietic response in elite adolescent swimmers. 49 To our knowledge, only a few studies have dealt with MA elite athlete permanent residents and, apart from our recent report 13 none involved the adolescent population. Schmidt et al.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been observed in several studies that low atmospheric pressure causes hypoxia (Girard, 2022;Billaut et al, 2022) and reaching a lower max VO 2 (Pühringer et al, 2022), but performing a cantonment of preparation at altitude with a duration of at least 4-6 weeks (Mujika et al, 2019;Deldicque, 2022). leads to the increase of biochemical parameters such as: 2.3-BPG, Hb, RBC, EPO (Płoszczyca et al, 2018;Baranauskas et al, 2022;Beidleman et al, 2017) and implicitly of the performance sports (Girard et al, 2020) and VO 2 max (Lukanova-Jakubowska et al, 2022;Mancera-Soto et al, 2022 )) Also, it has been observed that if the tendency of SpO 2 is to decrease in altitude conditions, the rate of lactate recovery is not influenced, which is why an individual response to hypoxia is obtained from each athlete.…”
Section: Discussionmentioning
confidence: 99%
“…A delimitation of the study is that only male adolescents were studied. Even if cardiorespiratory adaptations to endurance training were found to be comparable between girls and boys around APHV [47, 48], further studies should be done, including in adolescent girls, to investigate the influence of sex on neuromuscular adaptations in addition to the effects of growth and maturation, and endurance training. Another delimitation is that the study was not designed as a randomized, controlled exercise training intervention.…”
Section: Discussionmentioning
confidence: 99%